Recent Progress on the Synergistic Antitumor Effect of a Borneol-Modified Nanocarrier Drug Delivery System - Li, Jinxiu; Xie, Qian; Ma, Rong; Li, Yong; Yuan, Jianmei; Ren, Mihong; Li, Hongyan; Wang, Jiajun; Lu, Danni; Xu, Zhuo; Wang, Jian (Frontiers in Medicine, 2021)
Borneol, a traditional Chinese medicine, can enhance therapeutic efficacy by guiding the active ingredients to the target site. Reportedly, borneol improves the penetration capacity of the nasal, cornea, transdermal, intestinal, and blood-brain barriers. Although nanotechnology dramatically changed the face of oncology by targeting tumor sites, the efficiency of nanoparticles delivered to tumor sites is very low, with only 0.7% of the total particles delivered. Thus, based on the penetration ability and the inhibition drug efflux of borneol, it was expected to increase the targeting and detention efficacy of drugs into tumor sites in nanocarriers with borneol modification. Borneol modification nanocarriers for improving drug-targeting have become a research focus in recent years, but few studies in this area, especially in the antitumor application. Hence, this review first summarizes the recent development of nanocarriers with borneol modification. We focus on the updated works of improving therapeutic efficacy, reducing toxicity, inhibiting tumor metastasis, reversing multidrug resistance, and enhancing brain targeting to expand their application and provide a reference for further exploration of targeting drug delivery systems for solid tumor treatment.